2007
DOI: 10.1300/j013v44n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Adherence Among Women with HIV Infection in Puerto Rico: The Potential Use of Modified Directly Observed Therapy (MDOT) Among Pregnant and Postpartum Women

Abstract: Women are the fastest growing segment of the adult population acquiring HIV, and most women infected with HIV are in their reproductive years. The success of HAART is highly dependent upon the ability and willingness of the individual to adhere to complex antiretroviral regimens. Improved adherence among HIV-infected pregnant women will delay disease progression in the mother and should also reduce HIV transmission to the baby. Modified directly observed therapy (MDOT), may benefit this population. MDOT has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…Moreover, with the exception of marital status, there were no data on social support, a variable that may be critical to informing interventions for this population. For example, social support and disclosure have been identified in several qualitative studies and one quantitiatve study of HIVpositive pregnant women as important facilitators of adherence (Ciambrone et al, 2006;Wood et al, 2004). Interventions have been developed for other populations of HIV-infected adults that focus on increasing support around adherence through home visits, peer support interventions and couple support AIDS Care 965 interventions (Holstad, DiIorio, & Magowe, 2006;Remien et al, 2007;Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, with the exception of marital status, there were no data on social support, a variable that may be critical to informing interventions for this population. For example, social support and disclosure have been identified in several qualitative studies and one quantitiatve study of HIVpositive pregnant women as important facilitators of adherence (Ciambrone et al, 2006;Wood et al, 2004). Interventions have been developed for other populations of HIV-infected adults that focus on increasing support around adherence through home visits, peer support interventions and couple support AIDS Care 965 interventions (Holstad, DiIorio, & Magowe, 2006;Remien et al, 2007;Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions have been developed for other populations of HIV-infected adults that focus on increasing support around adherence through home visits, peer support interventions and couple support AIDS Care 965 interventions (Holstad, DiIorio, & Magowe, 2006;Remien et al, 2007;Williams et al, 2006). These strategies may be particularly important to HIVpositive pregnant and postpartum women who are often overwhelmed with caregiving responsibilities and may neglect their own health without support or in the context of non-disclosure of their HIV status to family and friends (Ciambrone et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the baby's health was cited as a motivator for adherence. 5 During postpartum, women tend to miss more medical visits, and adherence tends to be lower than during pregnancy. 1,[6][7][8][9][10] Between 10% and 50% of the women stopped their ART after childbirth, part of them on their own without physician's approval.…”
mentioning
confidence: 99%
“…However, the effect sizes observed in the relationships between the maternal-fetal attachment model and these maternal health behaviors ranged, respectively, from medium to medium-large. These findings offer only partial support to the study's hypothesis; however they add emerging credence to similar associations suggested in the qualitative research literature (Ciambrone et al, 2007;D'Auria et al, 2006;Kelly et al, 2012;Njie-Carr et al, 2013). It also suggests potential benefits in attending to the relationship a woman has with her unborn child perhaps as an additional component of her prenatal care to possibly help resolve her struggles with health behaviors.…”
Section: Associations Between Maternal-fetal Attachment and Health Besupporting
confidence: 80%
“…The proposed study examines the protective influence maternal-fetal attachment may exert on HIV-, pregnancy-, and infant-related health behaviors among pregnant women living with HIV/AIDS. The desire to protect their fetuses from the threat of transmission might motivate these women to improve ART adherence specifically, and pregnancy-related health behaviors generally (Ciambrone et al, 2007;Mellins et al, 2008).…”
Section: Theoretical Framework Of This Studymentioning
confidence: 99%